2016
DOI: 10.1002/1873-3468.12333
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the genetic code of Escherichia coli with phosphotyrosine

Abstract: Protein phosphorylation is one of the most important post-translational modifications in nature. However, the site-specific incorporation of O-phosphotyrosine into proteins in vivo has not yet been reported. Endogenous phosphatases present in cells can dephosphorylate phosphotyrosine as a free amino acid or as a protein residue. Therefore, we deleted the genes of five phosphatases from the genome of Escherichia coli with the aim of stabilizing phosphotyrosine. Together with an engineered aminoacyl-tRNA synthet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
79
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 36 publications
0
79
0
Order By: Relevance
“…One of our goals in this manuscript was to explore the possibility that EF-Tu might be a more general target for translation system engineering, especially given that interactions between EF-Tu and aminoacyl-tRNAs are tuned to perfectly match natural amino acids with cognate tRNAs (Schrader et al, 2009). Previous reports suggest that EF-Tu engineering can be beneficial for bulky amino acids (Doi et al, 2007) and charged amino acids as shown for phosphoserine (Park et al, 2011) and phosphotyrosine (Fan et al, 2016). Our results suggest that, it might be a more general target, although additional studies are needed to understand the generality of evolving EF-Tu alongside aaRSs to facilitate integration of a wide range of ncAA targets.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One of our goals in this manuscript was to explore the possibility that EF-Tu might be a more general target for translation system engineering, especially given that interactions between EF-Tu and aminoacyl-tRNAs are tuned to perfectly match natural amino acids with cognate tRNAs (Schrader et al, 2009). Previous reports suggest that EF-Tu engineering can be beneficial for bulky amino acids (Doi et al, 2007) and charged amino acids as shown for phosphoserine (Park et al, 2011) and phosphotyrosine (Fan et al, 2016). Our results suggest that, it might be a more general target, although additional studies are needed to understand the generality of evolving EF-Tu alongside aaRSs to facilitate integration of a wide range of ncAA targets.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, ncAA-tRNA substrates may not bind EF-Tu efficiently because it is a non-native substrate, preventing efficient delivery to the ribosome. While still a subject of debate for ncAA incorporation efforts (Rogerson et al, 2015), EF-Tu may thus require engineering to allow for the efficient incorporation of a given ncAA (Fan et al, 2016; Park et al, 2011). Beyond o-aaRSs, o-tRNAs, and EF-Tu, ribosomes must be able to accommodate the ncAA and in some instances ribosome engineering may be necessary.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar EF-Tu engineering has been conducted to effectively insert selenocysteine into proteins in a SECIS-independent manner [63]. Not surprisingly, these laboratory-evolved EF-Tu variants contain mutations of negatively-charged or neutral residues to positively-charged arginines in the amino acid binding pocket [6264]. In addition to EF-Tu engineering, tRNA optimization has also been successfully performed to enhance ribosomal incorporation of long-chain amino acids [65].…”
Section: Recognition Of Aminoacyl-trnas By Elongation Factormentioning
confidence: 99%